A Neglected Aspect of the Debates on the EU Budget: Duration of the MFF - Ákos Kengyel (Intereconomics, 2018)
In May 2018, the European Commission published its proposal on the Multiannual Financial Framework (MFF) for the period 2021-2027. Preparation for the post-2020 MFF requires comprehensive analysis of the characteristic features of the EU budget and of the priorities that should be supported at the EU level. The duration of the MFF has not received great attention in academic analyses and official documents, but it has strategic importance in terms of achieving goals and implementing policies. This article analyses the advantages and disadvantages of five-year, seven-year and ten-year MFF durations, as well as their consequences.
Keywords: 330